PENGARUH AUDIT INTERN TERHADAP PELAKSANAAN GOOD CORPORATE GOVERNANCE (Studi Survei pada Perbankan di kota Pekanbaru) - Tuminah Sinaga; Taufeni Taufik; Alfiati Silfi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The study was conducted using a survey method. With the aim to empirical evidence that the effect of internal audit include independence, professional proficiency, scope of work, execution of inspection activities, and management section of internal audit on the implementation of good corporate governance, the banks in the city of Pekanbaru. The population in this study were 20 banks in the city of Pekanbaru. Samples taken are 40 respondents. The type of data used is primary data by using questionnaire method of data collection. Data analysis methods are used alternately regression (multiple regression) with SPSS Version, 17.0 The results of this study indicate that the independence of the internal audit covering an effect on the implementation of good corporate governance with a t-value of 2,094, 2,034 T-table, a significant 0.044. Professional capabilities affect the implementation of good corporate governance, with a t-value of 6,793, 2,034 t-table, significant 0.000. Scope of work affect the implementation of good corporate governance with a t-value of 6,793, 2,034 t-table, a significant 0.000. Implementation of inspection activities affect the implementation of good corporate governance, with a t-value of 2.371, t-table 2034, a significant 0.024. Management of internal audit section affects the implementation of good corporate governance with a t-value of 2,194, 2,034 t-table singnifikan 0035Keywords: Independence, Professional Capability, Scope of Work, theimplementation of inspection activities, and management ofinternal audit section, and good corporate governance